The Role of Teachers in Fostering Students’ Discipline and Responsibility - Istghosah (Agrapana Media, 2025)
This study aims to analyze the role of teachers in fostering students’ discipline and responsibility through a Systematic Literature Review (SLR) approach. The research synthesizes findings from various empirical studies published between 2015 and 2025, focusing on how teachers design, implement, and reflect upon character education practices in primary and secondary schools. The results reveal that teachers play a central role as moral exemplars, facilitators, and designers of value-based learning environments. Effective strategies include modeling positive behavior, establishing consistent classroom routines, and promoting reflective and participatory learning activities. However, challenges such as limited time allocation, policy-practice gaps, and lack of institutional support hinder the sustainability of character education. The review also highlights the growing importance of digital literacy and ethical engagement in fostering responsibility in the modern learning context. Overall, this study emphasizes that teachers’ moral integrity, pedagogical innovation, and systemic collaboration are crucial in developing students’ discipline and responsibility as integral components of holistic education.